2009
DOI: 10.1108/09596110910975954
|View full text |Cite
|
Sign up to set email alerts
|

Hotel management company forecasting and budgeting practices: a survey‐based analysis

Abstract: PurposeThe purpose of this study is to investigate and document current US hotel management company practices in budgeting and forecasting, and to recommend a process to improve accuracy and efficiency.Design/methodology/approachKey corporate financial executives of hotel management companies operating in the USA were surveyed. Different from prior studies that surveyed the US property‐level managers, or European hotel operators, the study surveyed the authors of budget guidelines of US hotel management compan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0
23

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(59 citation statements)
references
References 23 publications
2
34
0
23
Order By: Relevance
“…The study by Uyar & Bilgin (2011) on hotel companies in Turkey reveals that 63% prepare budget manuals, which corroborates the research by Steed & Gu (2009), who noted the establishment of the budget guidelines by senior management in an average 4.5 points on a scale of one to five.…”
Section: Planning and Budget Preparationsupporting
confidence: 70%
See 4 more Smart Citations
“…The study by Uyar & Bilgin (2011) on hotel companies in Turkey reveals that 63% prepare budget manuals, which corroborates the research by Steed & Gu (2009), who noted the establishment of the budget guidelines by senior management in an average 4.5 points on a scale of one to five.…”
Section: Planning and Budget Preparationsupporting
confidence: 70%
“…The study by Steed & Gu (2009) showed that in 64.3% of hotel companies, the value indicated by the hotel owner was the most important influence in the guidelines for increasing revenue. Among the bases for such an increase, stand out REVPAR or increased percentage with 54.8%, percentage of increase over the previous year with 52.4%, based on ADR and occupancy percentage with 35.7%, respectively, improving the competitive set with 31%, another factor with 6.2% or the inflation forecast with 4.8%.…”
Section: Planning and Budget Preparationmentioning
confidence: 99%
See 3 more Smart Citations